2017
DOI: 10.29356/jmcs.v60i3.97
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antimicrobial and Chemical Composition of Essential Oils from Piper caldense Tissues

Abstract: The essential oils from leaves, stems and roots of Piper caldense were analyzed by GC-MS. The antibacterial potential of the oils was evaluated against gram-negative bacteria and gram-positive bacteria. The major chemical constituents that were identified from various parts of this plant were α-cardinal, α-muurolol, tujopsan-2-β-ol and δ-cadiene in the leaves, valencene, pentadecane, elina-3,7-11-dieno α-terpineol in the roots and terpine-4-ol, α-terpineol, α-cadinol 2-β-ol in the stems. Tissue oils showed ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Piper caldense oils from different tissues displayed as major components α-cadinol (19.0%), α-muurolol (9.0%), and thujopsan-2β-ol (7.4%) (leaves); terpinen-4-ol (18.5%), α-terpineol (15.3%), and α-cadinol-2β-ol (9.8%) (stems); and pentadecane (35.7%), valencene (10.5%), and selina-3,7(11)-diene (5.4%) (roots). The samples were tested against E. coli , Klebsiella pneumoniae , Pseudomonas aeruginosa , S. aureus and B. subtilis using agar diffusion assay and showed moderate to weak bacterial activity with MIC value of 325 or 750 μg/mL in comparison to gentamicin (5.0 μg/mL) [ 54 ]. P. cernuum and P. regnellii EOs from leaves inhibited growth of S. aureus and Candida albicans when evaluated by agar diffusion assay.…”
Section: Biological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Piper caldense oils from different tissues displayed as major components α-cadinol (19.0%), α-muurolol (9.0%), and thujopsan-2β-ol (7.4%) (leaves); terpinen-4-ol (18.5%), α-terpineol (15.3%), and α-cadinol-2β-ol (9.8%) (stems); and pentadecane (35.7%), valencene (10.5%), and selina-3,7(11)-diene (5.4%) (roots). The samples were tested against E. coli , Klebsiella pneumoniae , Pseudomonas aeruginosa , S. aureus and B. subtilis using agar diffusion assay and showed moderate to weak bacterial activity with MIC value of 325 or 750 μg/mL in comparison to gentamicin (5.0 μg/mL) [ 54 ]. P. cernuum and P. regnellii EOs from leaves inhibited growth of S. aureus and Candida albicans when evaluated by agar diffusion assay.…”
Section: Biological Activitiesmentioning
confidence: 99%
“… Pueblo Bello, Cesar, Colombia Aerial parts (MWHD) α-Pinene (20.3%), β-pinene (32.3%), β-caryophyllene (6.3%) Antifungal, broth dilution assay ( Trichophyton rubrum , MIC 157 μg/mL; Trichophyton mentagrophytes , MIC 125 μg/mL); cytotoxic (Vero cells, IC 50 15.2 μg/mL) [ 121 ] P. caldense C. DC. Recife, Pernambuco state, Brazil Leaf (HD) δ-Cadinene (5.6%), thujopsan-2β-ol (7.4%), α-muurolol (9.0%), α-cadinol (19.0%) Antibacterial, agar diffusion assay ( Bacillus subtilis , Staphylococcus aureus , Klebsiella pneumoniae ) [ 54 ] P. caldense C. DC. Recife, Pernambuco state, Brazil Root (HD) Valencene (10.5%), pentadecane (35.7%), selina-3,7(11)-diene (5.4%) Antibacterial, agar diffusion assay ( Bacillus subtilis , Staphylococcus aureus , Escherichia coli , Klebsiella pneumoniae , Pseudomonas aeruginosa ) [ 54 ] P. caldense C. DC.…”
Section: Table A1mentioning
confidence: 99%
“…In another study, the major compounds identified in the cultivar "Bragantina" were cubenol (14.55-21.53%), bicyclogermacrene (6.36-8.16%), and β-selinene (4.10-6.21%) [43]. The main component of "Bragantina" cultivar, α-muurolol, can also be found in other Piper species, such as P. amalago (5.0-9.3%) [44], P. caldense (9.0%) [45], P. cernuum Vell. (5.8%) [46], P. manausense (7.6%) [47], and P. sp.…”
Section: Resultsmentioning
confidence: 99%
“…Also, hexadecenoic acid and octadecanoic acid were found to disrupt cytoplasmic membranes and induce DNA damage to Staphylococcus aureus and Pseudomonas aeruginosa [ 71 ]. Additionally, hexadecenoic acid, methyl ester inhibited the growth of Escherichia coli , Pseudomonas aeruginosa and Klebsiella bacterial strains [ 72 , 73 ], whereas Pentadecane, Octadecane, and Eicosane possess anti-bacterial activity against the tested bacteria [ 74 , 75 ]. Certain carotenoids induced lysozyme accumulation in the cell that digests bacterial cell walls [ 76 ] whereas, β-carotene and Astaxanthin inhibited Pseudomonas aeruginosa bacterial growth [ 77 , 78 ] and Neoxanthin caused growth inhibition in helicobacter pylori growth [ 79 ].…”
Section: Discussionmentioning
confidence: 99%